Be Explicit: Identifying and Addressing Misaligned Goals in Collaborative Research Teams. Issue 1 (1st January 2023) - Haas, Nicholas
ABSTRACT: The misalignment of goals among researchers, external organizational partners (OPs), and study participants is thought to pose a challenge to the successful implementation of collaborative research projects. However, the goals of different collaborative team members almost never are elicited, making identification of misalignment and its potential consequences a difficult task. In this evaluation of a United Nations Nonviolent Communication Program conducted in Bangladesh, the Maldives, and Sri Lanka, I collected qualitative and quantitative data on OPs' and study participants' expected program impacts. I find that there are differences in OP and participant goals and that misalignment appears to bear some responsibility for participant dissatisfaction with the program. I also observe evidence that as the program progressed, participants' expected program impacts began to more closely approximate those of the OPs. I conclude with thoughts on the benefits of explicitly measuring research team goals and expectations and addressing their misalignment.